2017
DOI: 10.1111/jdv.14211
|View full text |Cite
|
Sign up to set email alerts
|

Rapid improvements in health‐related quality of life and itch with ixekizumab treatment in randomized phase 3 trials: results from UNCOVER‐2 and UNCOVER‐3

Abstract: Ixekizumab-treated patients achieved more rapid improvements both in HRQoL and itch compared with patients treated with ETN and PBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Although a neglected area of medicine, recent studies have demonstrated the frequency and burden of psoriatic itch. 28,29 Interestingly, certain localizations were more prominent than others. Anal pruritus and pruritus of the scalp are especially problematic because there are few scientific findings in these issues.…”
Section: Interpretation Of the Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a neglected area of medicine, recent studies have demonstrated the frequency and burden of psoriatic itch. 28,29 Interestingly, certain localizations were more prominent than others. Anal pruritus and pruritus of the scalp are especially problematic because there are few scientific findings in these issues.…”
Section: Interpretation Of the Resultsmentioning
confidence: 98%
“…Of the group of dermatoses, it is of interest that psoriasis was searched for as frequently as atopic dermatitis, once more supporting the role of pruritus in this disease. Although a neglected area of medicine, recent studies have demonstrated the frequency and burden of psoriatic itch . Interestingly, certain localizations were more prominent than others.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current analysis investigates the differential effects of two active treatments for moderate-to-severe psoriasis and the effects at different time points, which, to our knowledge, is rarely explored in SEM analyse. Leonardi and colleagues 26 focused on the effects of pruritus severity only, whereas the present study integrated three bothersome psoriasis-related symptoms and their interactions. 12,13 The confirmation of the hypothesis that the symptoms and feelings subscale was antecedent to a latent variable (factor) representing the remaining five subscales of the DLQI Total (revised) was a notable result of this analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the current analysis investigates the differential effects of two active treatments for moderate‐to‐severe psoriasis and the effects at different time points, which, to our knowledge, is rarely explored in SEM analyse. Leonardi and colleagues focused on the effects of pruritus severity only, whereas the present study integrated three bothersome psoriasis‐related symptoms and their interactions …”
Section: Discussionmentioning
confidence: 99%
“…Within 1 year of treatment, up to 80% of patients treated with IL‐17 or IL‐23 inhibitors can expect almost clear skin, as indicated by a 90% improvement in Psoriasis Area and Severity Index (PASI 90), and 50–60% of patients can expect completely clear skin (PASI 100) . Although clinical trial data and systemic reviews have suggested that IL‐17 inhibitors can improve a patient's psoriasis more rapidly than IL‐23 inhibitors, no trials have directly tested the speed of efficacy of IL‐17 vs. IL‐23 inhibitors in inducing complete plaque psoriasis clearance.…”
mentioning
confidence: 99%